Survei Entomologis dan Status Kerentanan Larva Aedes aegypti terhadap Insektisida Organofosfat di Desa Banguntapan Yogyakarta - Novyan Lusiyana (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2019)
Aedes aegypti is a vector of many arboviruses. Information of the breeding site of this vector is important for preventing many diseases and for design intervention programs. This study was to determine the breeding place of Ae. aegypti, type of water-holding container and susceptibility for organophosphate insecticide in Banguntapan village. Design of this research was cross-sectional study that located in Banguntapan village from November 2016 until January 2017 on 400 houses. All water holding container that present in and around houses were inspected for the presence of Ae. aegypti with single larvae method. Susceptibility test using bioassay and biochemist test was applied on F1 generation larvae. Risk indicator of the entomological survey was the free larvae index (FLI), house index, container index and breteau index. A total 696 container were inspected, of which 149 containers were positive Ae. aegypti, with FLI 73%, HI 27%, BI of 33%, CI 18.14% and PI of 17.5%. The most common breeding habitats for larvae were bathtub, bucket, plant’s pot, birds drinking pot. Susceptibility status to temephos was susceptible, whiles for organophosphate insecticide was medium resistance. Banguntapan village was a high potential for arbovirus transmission and bathtub is the most potential breeding place for Ae. aegypti mosquitoes.